Protective effect of Nr4a2 (Nurr1) against LPS-induced depressive-like behaviors via regulating activity of microglia and CamkII neurons in anterior cingulate cortex. (May 2023) - He, Yong; Wang, Yue; Yu, Heming; Tian, Yu; Chen, Xiangyu; Chen, Chong; Ren, Yikun; Chen, Zhi; Ren, Yi; Gong, Xue; Cheng, Ke; Liu, Xiaolei; et al.
Abstract: Neuroinflammation is tightly associated with onset of depression. The nuclear receptor related 1 protein (Nurr1, also called Nr4a2), its roles in dopaminergic neurons is well understood, which can alleviate inflammation. Nevertheless, potential effects of Nr4a2 on neuroinflammation associated with depression still remains unclear. Chronic lipopolysaccharides (LPS) stress induced depressive-behaviors were confirmed via behavioral tests. Differentially expressed genes were detected by using RNA-sequencing. The anterior cingulate cortex (ACC) tissues were collected for biochemical experiments. The Golgi-Cox staining and virus labeling were used to evaluate the dendritic spines. We applied fluoxetine (FLX) and amodiaquine dihydrochloride (AQ, a highly selective agonist of Nr4a2) in mice. Overexpression experiments were performed by injecting with AAV-Nr4a2-EGFP into ACC. Chemogenetic activation of CamkII neurons via injecting the hM3Dq virus. Mice treated with LPS displayed depressive- and anxiety-like behaviors. The reduction of Nr4a2 and FosB induced by LPS were rescued by pretreatment with FLX or AQ. More importantly, LPS-induced behavior deficits in mice were also alleviated via fluoxetine treatment and pharmacological activation the expression of Nr4a2. Meanwhile, enhancing the level of Nr4a2 could improve dendritic spines loss of neuron and morphological changes in microglia. Overexpression of Nr4a2 in ACC reversed the depressive- and anxiety-like behaviors caused by LPS administration. Activation of CamkII neurons in ACC could robustly increase the expression of Nr4a2 and improve LPS-induced behavior deficits. Our findings demonstrate that the Nr4a2 may regulate depressive-like behaviors via alleviating the impairment of morphology and function on microglia and CamkII neurons induced by chronic neuroinflammation. Graphical Abstract: ga1